EMA Recommendation for the Pediatric Indications of Plerixafor (Mozobil) to Enhance Mobilization of Hematopoietic Stem Cells for Collection and Subsequent Autologous Transplantation in Children with Lymphoma or Malignant Solid Tumors. (10th March 2020) - Karres, Dominik; Ali, Sahra; van Hennik, Paula B.; Straus, Sabine; Josephson, Filip; Thole, Geanne; Glerum, Pieter J.; Herberts, Carla; Babae, Negar; Herold, Ralf; Papadouli, Irene; Pignatti, Francesco
Abstract: : On March 28, 2019, the Committee for Medicinal Products for Human Use adopted a positive opinion recommending the marketing authorization for the medicinal product plerixafor. The marketing authorization holder for this medicinal product is Genzyme Europe B.Th. The adoption was for an extension of the existing adult indication in combination with granulocyte colony‐stimulating factor (G‐CSF) to pediatric patients (aged 1 year to <18 years) to enhance mobilization of hematopoietic stem cells to the peripheral blood for collection and subsequent autologous transplantation in children with lymphoma or solid malignant tumors. This treatment is indicated either preemptively, when circulating stem cell count on the predicted day of collection after adequate mobilization with G‐CSF (with or without chemotherapy) is expected to be insufficient with regard to desired hematopoietic stem cells yield, or in children who previously failed to collect sufficient hematopoietic stem cells. The efficacy and safety of plerixafor were evaluated in an open label, multicenter, phase I/II, dose‐ranging, and randomized controlled study (DFI12860) in pediatric patients with solid tumors, including neuroblastoma, sarcoma, Ewing sarcoma, or lymphoma, who were eligible for autologous hematopoietic stem cell transplantation. Forty‐five patients (aged 1 year to <18 years) were randomized, 2:1, using 0.24 mg/kg of plerixafor plus standard mobilization (G‐CSF with or without chemotherapy) versus control (standard mobilization alone). The primary analysis showed that 80% of patients in the plerixafor arm experienced at least a doubling of the peripheral blood (PB) CD34+ count, observed from the morning of the day preceding the first planned apheresis to the morning prior to apheresis, versus 28.6% of patients in the control arm ( p = .0019). The median increase in PB CD34+ cell counts from baseline to the day of apheresis was 3.2‐fold in the plerixafor arm versus by 1.4‐fold in the control arm. The observed safety profile in the pediatric population was consistent with that in adults, with adverse events mainly related to injection site reactions, hypokalemia, and increased blood bicarbonate. Importantly, plerixafor exposure did not seem to negatively affect transplant efficiency. This article summarizes the scientific review of the application leading to regulatory approval in the European Union. Implications for Practice: This review of the marketing authorization of plerixafor will raise awareness of pediatric indication granted for this medicinal product. Abstract : This article addresses development and authorization of novel agents for the treatment of cancer in the pediatric population, summarizing the scientific review of the application leading to regulatory approval of plerixafor in the European Union.